2022
DOI: 10.3390/ijerph192416490
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical Activity at School on Eating Behaviour and Leisure Time of Early Adolescents

Abstract: (1) Background: Diet and physical activity (PA) significantly impact health. The aim of this study was to evaluate the impact of long-term increase in organized PA level at school on the eating behaviour and leisure time of early adolescences in the period from the age of 10 to 12. (2) Methods: Children born in 2007 (n = 278) in groups with a standard (control group) and increased level of organized PA at school (4 and 10 h a week) were subjected to an anonymous follow-up survey. The questionnaire included 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…After all, usually, parents prepare breakfast for high school students and make sure they eat it. These results were consistent with those of Portuguese teenagers in many school years, who also did not skip breakfast [38], but contradictory to the results of Polish studies indicating skipping breakfast by teenagers, especially those not engaged in physical activity [39][40][41]. Other Polish research showed the same trend of skipping breakfast by adult Poles [42].…”
Section: Discussionsupporting
confidence: 67%
“…After all, usually, parents prepare breakfast for high school students and make sure they eat it. These results were consistent with those of Portuguese teenagers in many school years, who also did not skip breakfast [38], but contradictory to the results of Polish studies indicating skipping breakfast by teenagers, especially those not engaged in physical activity [39][40][41]. Other Polish research showed the same trend of skipping breakfast by adult Poles [42].…”
Section: Discussionsupporting
confidence: 67%
“…An additional condition influencing children's PF, besides the number of PE lessons at school, is the frequency of PA undertaken during leisure time. It was also measured and described by the authors of this study in another paper [70]. It was observed that, starting from a similar level in both GC and SC groups the frequency of PA during leisure time increased in the SC and decreased in GC during the course of the study.…”
Section: Discussionmentioning
confidence: 59%
“…Children's extracurricular sporting activities was assessed only in part as the frequency of leisure time PA. The results were presented in a previous paper [70]. However, the direct and detailed measurement of sport activities during leisure time was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the apparent reason for the observed effects, i.e., the additional physical activity in the EG, another factor may also play a role. It can be speculated that participation in daily exercise and performing fun movement impulses during every lesson every day for the intervention period of one year leads to a higher personal affinity to exercise and, therefore, being physically more active outside the school setting as well [ 42 ]. It would be especially desirable if this effect could be achieved with children that would otherwise not have considered sports and exercise a leisure activity, thereby creating a positive trajectory towards a healthier lifestyle.…”
Section: Discussionmentioning
confidence: 99%